On the Distribution of Income in Five Countries - Mariacristina DeNardi; Liqian Ren; Chao Wei (Luxembourg Income Study (LIS), 2000)
The goal of this study is to look at different countries, study their redistribution policies and discuss the effects of the redistribution/incentives tradeoff. Since we want to look at countries that display different degrees of government intervention, we pick countries belonging to both traditions. We focus on a small number of countries to study these issues in detail: the U.S., Canada, Germany, Sweden and Finland. We focus on distribution of income across working-age households in these five countries because we are interested in labor income (earnings) inequality, abstracting from normal retirement decisions. Looking only at households of working age, however, we ignore another important aspect of redistribution: social-security transfers to older people.
Keywords: 330; Einkommensverteilung; Einkommensumverteilung; USA; Kanada; Deutschland; Schweden; Finnland